Characteristics of BrC and BC emissions from controlled diffusion flame and diesel engine combustion. Issue 7 (2nd June 2021) - Malmborg, Vilhelm; Eriksson, Axel; Gren, Louise; Török, Sandra; Shamun, Sam; Novakovic, Maja; Zhang, Yilong; Kook, Sanghoon; Tunér, Martin; Bengtsson, Per-Erik; Pagels, Joakim
Abstract: Constraining the climate impact of particulate brown carbon (BrC) will require identification of formation mechanisms and isolation of its different components to allow for source apportionment. For fresh combustion aerosols, the light absorption characteristics and the Absorption Ångstrom Exponent (AAE) are principally controlled by the combustion conditions in which the particles formed and evolved. We investigated the influence of combustion temperatures on the BrC or black carbon (BC) emission characteristics for a miniCAST soot generator (propane fuel) and a modern heavy-duty diesel engine (petroleum diesel and two renewable diesel fuels). Changes in the AAE, mass spectral signatures, and thermal-optical characteristics were studied. We show that changing operating parameters to gradually reduce the combustion temperatures in these two fundamentally different combustion devices result in a regression from BC dominated to BrC dominated particle emissions. The regression toward BrC was associated with: (1) an increasing mass fraction of particulate non-refractory polycyclic aromatic hydrocarbons (PAHs), (2) an increasing fraction of refractory organic carbon, (3) more curved soot nanostructures and shorter fringe lengths, and (4) increased signal from (refractory) large carbon fragments in IR laser-vaporization aerosol mass spectra. Based on these results we argue that fresh BrC dominated combustion aerosols are attributed to primary emissions from low temperature combustion, highlighting the influence of refractory constituents and soot nanostructure. Higher temperatures favor the growth of conjugated polyaromatic structures in the soot, a progression hypothesized to control the evolution from BrC to BC character of the emitted aerosols.